Plasma functionalized MoSe2 for efficient nonenzymatic sensing of hydrogen peroxide in ultra‐wide pH range. Issue 3 (25th January 2022) - Luo, Yang; Wu, Donghai; Li, Zehui; Li, Xiao‐Yan; Wu, Yinghong; Feng, Shien‐Ping; Menon, Carlo; Chen, Houyang; Chu, Paul K.
Abstract: Enzymatic sensors have inherent problems such as the low stability and limited pH range in industrial and biomedical applications and therefore, more efficient nonenzymatic sensors are highly desirable. Herein, plasma‐functionalized defective MoSe2 is prepared and studied as a highly efficient catalyst for electrochemical sensing of H2 O2 . Experiments and theoretical computations show that the plasma‐induced Se multi‐vacancies and nitrogen dopants generate new active sites, expose more edge active surfaces, narrow the bandgap, and strengthen binding with the ·OH intermediate, which imparts new fundamental knowledge about the roles of defects in catalysis. The defective MoSe2 ‐catalyzed sensor delivers competitive performance in hydrogen peroxide detection such as a low detection limit of 12.6 nmol/L, wide operational pH range of 1−13, good long‐term stability, and high selectivity. The portable sensor produced by screen printing confirms the excellent commercial potential and in addition, the results not only reveal a novel concept to design and fabricate high‐performance sensors for H2 O2 but also provide insights into the effectiveness of surface modification of diverse catalytic materials. Abstract : Plasma functionalized defective MoSe2 is prepared for electrochemical sensing of H2 O2 . The Se vacancies and N dopants generate new active sites, expose more edge active surfaces, narrow the bandgap, and strengthen binding with ·OH. The sensor delivers competitive sensing performance in ultra‐wide pH range and a portable SPE sensor is developed to demonstrate the commercial potential.